Yes! Maximizers Maximize Almost Everything: The Decision-Making Style Is Consistent in Different Decision Domains - Moyano-Díaz, Emilio; Mendoza-Llanos, Rodolfo (Frontiers in Psychology, 2021)
The decision-making literature distinguishes one maximizing style from another satisficing decision-making style, but it is unknown whether these styles remain stable or are variable depending on the occasion. One way to approach it is to verify these styles' eventual generalization in people's behavior in different decision domains. Some incipient results with university students from the United States and Austria suggest that these styles would remain in three different domains. However, it is unknown if this is the case in adults, other cultures, or vital areas of great relevance, such as health and personal finances. The objective here is to identify if Chilean Latin American participants of different sex and age maintain their decision-making style in five different decision domains. The sample was 343 volunteers, 52.6% men, from two regions of central-southern Chile (Maule and Ñuble), aged between 20 and 90 years (M = 45.47; SD = 16.05), who answered the Maximization Tendency Scale, and 45 items corresponding to five different decision domains: health, life decision, finances, services & experiences, and consumers good. An apparent coherence of decision-making style - maximizing and satisficing - was obtained in the five domains. The health domain stands out for being the one in which it is maximized and with greater internal homogeneity.